Development and validation of a yoga module for children with visual impairment: A feasibility study. (January 2019) - Mohanty, Soubhagyalaxmi; Venkataramanujam, Sasipriya; Pradhan, Balaram; Hankey, Alex
Yoga has been found to be an effective intervention in children with visual impairment. Yoga modules used in previous studies were based on individual researcher's experience. However, no mention was given of them being endorsed by other specialists in the field. This study aimed to develop, validate, and assess the feasibility of a yoga module exclusively for children with visual impairment. A yoga module was developed based on traditional and contemporary yoga literature and published studies with the objectives of determining needs of the participants and yoga practices that could prove efficient. Its validation was carried out with 25 experts over two rounds of iteration and feasibility of the practices evaluated on nine children with visual impairment. Tennis ball throw and standing vertical jump tests were done to evaluate success of yoga practice. A total of 30 yoga practices with content validity ratio ⩾ 0.37 were retained in the final yoga module. All experts opined that the final module is technically easy to teach, learn, and practice. All the children reported 80% of satisfaction level with the yoga practices and the procedure used to teach them at the end of the intervention. The score in tennis ball throw increased significantly ( p  = .011) after the intervention, but the standing vertical jump score ( p  = .585) did not. Positive exit survey responses and good participation rates support the module's feasibility. Based on evidence from the traditional knowledge and scientific studies, the yoga module was validated for the children with visual impairment. The feasibility of the module was also assessed successfully which can be used safely and effectively as an alternative training for individuals with visual impairment.